ESTIMASI DAYA DUKUNG PERAIRAN PESISIR KECAMATAN BANYUPUTIH UNTUK TAMBAK UDANG BERDASARKAN LAJU BIODEGRADASI LIMBAH - Abdul Muqsith; Nuddin Harahab; Mohammad Mahmudi; Muhammad Fadjar (Fakultas Pertanian Universitas Yudharta Pasuruan, 2018)
This research was conducted in May 2018 in the coastal area of ​​Banyuputih Subdistrict, Situbondo Regency with the aim of estimating the land area and production capacity of shrimp ponds that can be supported by Banyuputih coastal waters based on the rate of biodegradation of organic waste in the form of Total Suspended Solid (TSS). The results showed that the area of ​​intensive ponds (stocking density of 126 birds / m2) that could be supported by waters was 39.30 hectares with shrimp production capacity of 739.72 tons / planting season, whereas for semi-intensive ponds (stocking density of 25 birds / m2) was 313.98 hectares with a maximum shrimp production capacity of 803.85 tons / planting season, and for traditional plus ponds (stocking density of 8 birds / m2) is 743.14 hectares with a maximum capacity of shrimp production of 578.90 tons / planting season. The simulation results of the three shrimp cultivation technologies (traditional plus, semi-intensive and intensive), obtained a combination of shrimp farm area that is still within the limits of environmental carrying capacity, namely: 5% (37.16 hectares) for traditional plus-tech shrimp farm land (8 tail / m2), 50% (157 hectares) for semi-intensive technology shrimp farms (25 individuals / m2), and 45% (17.69 hectares) for intensive technology shrimp farms (126 individuals / m2). The total land area of the third combination of technology is 211 hectares with shrimp production of 763.75 tons/planting season. The results of this study can be used as a reference for the development of shrimp ponds in a sustainable manner in the study area.